Physically Unclonable Functions From Basic Design Principles to Advanced Hardware Security Applications - Halak, Basel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book discusses the design principles of physically unclonable functions (PUFs) and how these can be employed in hardware-based security applications, in particular, the book: Provides readers with a comprehensive overview of security threats on embedded systems and existing countermeasures; Includes an intensive tutorial on how to design and evaluate physically unclonable functions, supported by circuit diagrams and exemplar hardware implementations; Discusses the reliability challenges facing PUF technology and explains in details the state of the art mitigation approaches adopted, including those based on error correction codes and/or pre-processing techniques; Gives a comprehensive tutorial on the security threats facing PUF technology, including modelling attacks using machine learning algorithms, side channel analysis, and physical attacks. It also outlines possible countermeasures and defence mechanisms; Explains in detailed the practical applications of PUF technology, these include secure cryptographic key generation and storage, hardware-assisted security protocols, low cost secure sensors, anti-counterfeit integrated circuits and anti-tamper hardware. This book has many features that make it a unique source for students, engineers and educators, including more than 80 problems and worked exercises, in addition to, approximately 200 references, which give extensive direction for further reading. .
A Primer on Cryptographic Primitives and Security Attacks -- Physically Unclonable Functions: Design Principles and Evaluation Metrics -- Reliability Challenges of Silicon-Based Physically Unclonable Functions -- Reliability Enhancement Techniques for Physically Unclonable Functions -- Security Attacks on Physically Unclonable Functions and Possible Countermeasures -- Hardware-based Security Applications of Physically Unclonable Functions -- Appendix 1 -- Appendix 2 -- Appendix 3.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Signal processing; Electronic Circuits and Systems; Processor Architectures; Signal, Speech and Image Processing